Scientific Approaches to the Interpretation of the Essence of Environmental Management of the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article reviews current definitions of environmental management: institutional, processual, system and functional; it’s offered to interpretate ecological management from the perspective of institutional and processual views. Under the institutional view, environmental management of the enterprise is a set of principles, forms, methods, techniques and tools of influence, which, on the one hand, used by the personnel to achieve high work performance, on the other – to provide safe ecological activity basing on rational and sustainable nature management that does not harm the environment. Elements of the environmental management of the enterprise (subject, object, a subject, the purposes, tasks, objectives, instruments, tools, methods, the expected results) are defined. According to the processual view, environmental management of the enterprise is a set of consecutive interconnected stages of administrative activity, which provides justification, adoption and implementation of management decisions for ecologically safe and cost-effective strategy of the ecological management of the enterprise, namely: formation of ecologically oriented conception of development of the enterprise; strategic analysis of the environment; diagnostic of the ecological and economical security of the enterprise; forecasting of changes in the strategic environment of the enterprise; ecologically purpose-setting; justification of a strategic plan of development of the enterprise; development of ecological policy; strategic planning of realization of the chosen strategy; ecological monitoring, audit and control of strategies of implementation of the ecological policy; evaluation of the effectiveness of the chosen strategy of the ecological policy.
Keywords: enterprise, environmental management, ecological management strategy, ecological management of the enterprise